Comparative analysis of experimental and theoretical data when investigating of the structure of beryllium ceramics in the channel of installation casting - Саттинова, З.К.; Рамазанова, Г.И.; Асилбеков, Б.К.; Ордабек, А.К. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Experimental research of the effect of casting regimes on the temperature field in the zone of solidification of the molding was made on the experimental bushing, by measuring the temperature using a thermocouple installed on the different levels by the height of crystallizer. According to the obtained data, dependence of position of the boundary of solidification slurry from different parameters of casting was built. The shape of the curve of surface solidification, which is dependent on the casting parameter, is defined taking into account that the temperature changes linearly by the height and radius of crystallizer on the short segments. The influence of molding velocity on the thermal regime of the casting was determined in the first series of experiments. Temperature distribution, estimated during the experiments, in the form-building cavity of bushing depending on the molding velocity and heat extraction conditions on the walls of form-building of annular cavity lets us determine the transition from liquid (viscous-plastic) state to solid-plastic one. The experiment results were analyzed and generalized using mathematical model of the thermoplastic slurry molding process. The results of calculation are in agreement with the experimental data, and they show physical validity of the proposed mathematical model of the molding process of the beryllia thermoplastic slurry.